2022
DOI: 10.1038/s41598-022-10499-z
|View full text |Cite
|
Sign up to set email alerts
|

Preceding propagation of turbulence pulses at avalanche events in a magnetically confined plasma

Abstract: The preceding propagation of turbulence pulses has been observed for the first time in heat avalanche events during the collapse of the electron internal transport barrier (e-ITB) in the Large Helical Device. The turbulence and heat pulses are generated near the foot of the e-ITB and propagate to the peripheral region within a much shorter time than the diffusion timescale. The propagation speed of the turbulence pulse is approximately 10 km/s, which is faster than that of the heat pulse propagating at a speed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…, where v Thi is the ion thermal velocity, a is the minor radius, and ρ s is the ion gyro radius [22,40]. However, it has been reported that the model estimated velocity of turbulence spreading matches well with the heat pulse propagation.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…, where v Thi is the ion thermal velocity, a is the minor radius, and ρ s is the ion gyro radius [22,40]. However, it has been reported that the model estimated velocity of turbulence spreading matches well with the heat pulse propagation.…”
Section: Discussionmentioning
confidence: 93%
“…The MHD collapse event are known to generate turbulence and heat avalanche events [22]. These turbulence and heat pulse are observed to be propagating to the peripheral region faster than the diffusion time scales, with the turbulence preceding the heat pulse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We are beginning design of a next generation pulse-burst laser system, aiming for a maximum rep rate of 100 kHz for 1 ms. Pulse-burst laser systems with "fast burst" rep rates in the range of 10-20 kHz have been built for the Thomson scattering diagnostics on MST [1], NSTX-U [2], and LHD. Recent measurements on LHD illustrate the new diagnostic capability to capture fast dynamics in the plasma [3,4].…”
Section: Introduction To Pulse-burst Laser Systemsmentioning
confidence: 99%